Paraphrased Texts in the Literature Review Section of Undergraduate Theses Written by EFL Students at the English Language Education Program of Universitas Negeri Padang - Tiara Zelfina Asmanda; Muhammad Al Hafizh (Universitas Negeri Padang, 2021)
This research was conducted to find out types of paraphrases and paraphrasing techniques in EFL students' paraphrased texts. It was content analysis and descriptive research. The data were obtained from 11 undergraduate theses written by students of the UNP English Language Education Program in the graduation period of March 2020 to March 2021. The total data found were 49 paraphrases which were analysed by using Keck's (2006) Taxonomy of Paraphrase Types and Pieterick's Paraphrasing Techniques in Injai (2015). Regarding the types of paraphrases, these texts were 55% Near Copy, 20% Minimal Revision, 20% Moderate Revision, and 4% Substantial Revision. Meanwhile, there are 10 types of paraphrasing techniques used by these texts (7 sub-techniques of Syntactic Paraphrasing and 3 sub-techniques of Semantic Paraphrasing). Moreover, the most frequently used paraphrasing techniques were